Kepatuhan masyarakat desa delod peken kecamatan tabanan dalam penggunaan masker selama pandemi covid-19 patuhan Masyarakat Desa Delod Peken Kecamatan Tabanan dalam Penggunaan Masker Selama Pandemi Covid-19: Community compliance of delod peken village, tabanan sub district in using masks during the covid-19 pandemic - Ni Made, Sintha Pratiwi; Dewi, I Dewa Ayu Nyoman Manik Ulan (Bali Medika Jurnal, 2021)
Background: currently, a new type of coronavirus that significantly affects several aspects of human life shocks the world. The number of COVID-19 patients in Indonesia is increasing. One of the provinces with the highest number of confirmed cases in Bali is in 10th place with 10,605 confirmed cases. Of the nine regencies/cities in Bali Province, Tabanan Regency is one of the regencies included in the COVID-19 red zone. Tabanan is the sub-district with the highest number of confirmed cases of COVID-19, with Delod Peken Village as the village with the highest number of close contacts. Efforts that the government has made have not been fully able to reduce the number of COVID-19 cases. Based on a preliminary study conducted in Delod Peken Village, most people have not complied with the use of masks. Objective: This study aims to identify the compliance of the Dead Peken Village community in the use of masks during the COVID-19 pandemic. Methods: This type of research is quantitative research with an analytical descriptive design. The number of samples in this study was 110 respondents. The sampling technique used is purposive sampling. Results: community compliance in Delod Peken Village, Tabanan Sub District, in masks during the COVID-19 pandemic shows that 54 respondents (49.1%) had compliance in the obedient category in the use of masks, 41 respondents (37.3%) were in the less compliant category, and as many as 15 respondents (13.6%) did not comply with the use of masks during the COVID-19 pandemic. Conclusion: This study shows that the people of Delod Peken Village, Tabanan Sub District, are mostly obedient in using masks during the COVID-19 pandemic. Keywords: COVID-19; Community Compliance; Use of Masks; Health Protocol